Kawasaki disease complicated with shock syndrome, macrophage activation syndrome, and acute abdomen in children: Two case reports - Yi, Cong; She, Xiang; Chen, Jia (Frontiers in Pediatrics, 2023)
Background：Kawasaki disease (KD) is an acute systemic vasculitis that can involve multiple organs. Few reports have been published about KD patients presenting with multiple complications such as acute abdomen, KD shock syndrome (KDSS), and macrophage activation syndrome (MAS). Case Description: We present the cases of two males (9 and 12 years old) diagnosed with KD accompanied by rare manifestations. Case 1 is a 9-year-old male treated for acute appendicitis, KDSS, and MAS. Case 2 is a 12-year-old male who presented with KDSS, MAS, and an ileal perforation. They were treated with intravenous immunoglobulin, aspirin, high-dose corticosteroids, vasoactive drugs, and symptomatic treatment, with good outcomes. Conclusions: Clinicians should be aware of the possibility of KD in the presence of fever and unusual manifestations, such as severe inflammatory indicators and acute abdomen that is nonresponsive to antibiotic therapy. Meanwhile, KD-related unusual complications should be recognized, such as KDSS and MAS.